Generation of UNL Attributes and Resolving Relations for Punjabi Enconverter - Kumar, Parteek; Sharma, R. K. (Malaysian Journal of Computer Science, 2011)
Automated Machine Translation (AMT) has a potential to digitally unite the whole world. Universal Networking Language (UNL) has been used by various researchers as an interlingual approach for AMT. The UNL system consists of two main components, namely, EnConverter (used for converting the text from a source language to UNL) and DeConverter (used for converting the text from UNL to a target language). This paper discusses the framework for designing EnConverter for Punjabi language with a special focus on generation of UNL attributes and relations from Punjabi source text. The architecture of Punjabi EnConverter, algorithm for understanding the Punjabi input sentence and resolution of UNL relations and attributes is also discussed in this paper. The paper highlights the EnConversion analysis rules for the EnConverter and indicates its usage in the generation of UNL expressions. This paper also covers the results of implementation of Punjabi EnConverter and compares these with the system available at Spanish Language Server.